Analysis of the management strategy for retribution revenue from sports venues in Papua Province - Yetty Margen Aronggear; Elsyan R Marlissa; Risky Novan Ngutra (Goodwood Publishing, 2025)
Purpose: This study aims to examine the implementation and contribution of retribution from sports facilities and infrastructure in supporting the Regional Original Revenue (PAD) of Jayapura City, as well as to identify the supporting and inhibiting factors affecting its effectiveness. Research methodology: The research employs a qualitative descriptive approach, using data collection techniques such as interviews, observations, and document analysis involving relevant stakeholders from the Youth and Sports Office and the Regional Financial Management Agency of Jayapura City. Results: The findings indicate that while the collection of retributions has been implemented according to standard procedures, its contribution to PAD remains relatively low. This is attributed to several obstacles, including insufficient operational budgets, limited human resources, underutilization of sports facilities, and the public's economic limitations. Conclusions: Retribution from sports facilities has the potential to support regional income; however, its effectiveness is constrained by institutional and socio-economic factors. With improved budgeting, monitoring, and utilization of facilities, this revenue source could make a more substantial contribution to Jayapura City's PAD. Limitations: This study is limited to the scope of Jayapura City and specifically focuses on retributions from sports facilities. Therefore, the results may not be generalizable to other regions or types of local revenues. Furthermore, the reliance on qualitative methods limits the extent of financial quantification and broader statistical analysis. Contribution: This research contributes to policy evaluation in optimizing local non-tax revenues. It also offers practical insights for improving retribution governance, particularly in the sports services sector.